Management Practices of Indigenous Cattle adopted by the Farmers in Thar Desert region of Rajasthan State - Kumar, Sunil (Indian Journal of Dairy Science, 2017)
Among the indigenous cattle, Sahiwal, Tharparkar and Rathi are the most important cattle breed of Thar Desert of Rajasthan, which can withstand harsh desert climatic conditions and provides livelihood security to the rural masses. In order to document the existing management practices followed by the farmers in the study area a comprehensive study was conducted in three districts of Rajasthan State i.e. Sri-Ganganagar, Jodhpur and Bikaner, the breeding tract of three indigenous cattle. A total of 180 respondents rearing indigenous cattle were selected randomly from six villages of three districts. The information regarding the important management practices of farmers in terms of indigenous cattle breeding practices, housing system adopted and health care aspects were collected using semi-structured interview schedule. The major findings of the study the indicates that, in case of breeding practices adopted, natural and indiscriminate mating of cows was dominated over planned mating with pedigree bull. In the case of heat and pregnancy diagnosis majority of them followed indigenous methods.Â  Majority of the cattle house structure of kuchha type kept under loose/ open housing system built in the direction of north to south. With respect to health care, majority of the farmers expressed their inability to access to departments veterinary services and hence predominantly depended on local healers and resorted to adoption of traditional/ethno veterinary practices for treating the indigenous cattle.